Identification of HR management best practices in marketing tourism production and services: scientific proof of progress in tourism destinations in several provinces in Indonesia - Faqih Nabhan; B.M.A.S. Anaconda Bangkara; Sri Sugiarti; Laros Tuhuteru; Meli Siagawati (Enrichment : Journal of Management, 2023)
Finding best practices in human resource management, especially in advancing global tourism, both services and goods, is an exciting topic, mainly when much scientific evidence has been investigated in various advanced provinces in the tourism industry. To obtain valid data to support this research question, we collect several publications which are scientific evidence in the field and analyze them using a phenomenological approach which includes, among others, in-depth data coding systems, in-depth evaluation, and data synthesis and interpretation to obtain valid findings to answer the research problem. We electronically scoured many literary data sources for our data. Next, we made a descriptive qualitative report, in which we looked at various points of view with findings including that the key to tourism success, as in several provinces in Indonesia, lies in the skills and excellence of government and private human resources in managing tourism to make their province the best tourist destination. Those are some reviews from various studies that are scientific evidence to answer this study question. Hopefully useful for further studies.